Avaliação mecânica tridimensional de molas T compostas de NiTi e Aço - Ribeiro, Alexandre Antonio [UNESP] (2015)
The space closure with Nickel-Titanium alloy (NiTi) T-loop springs for en masse retraction has not been studied. Superelasticity and shape memory are NiTi properties interesting to tooth movement. The aim was to determine by assessing three dimensionally the best T-loop spring design to the en masse space. Were tested one hundred T-loop composed springs by handles of rectangular NiTi wires and stainless steel horizontal rods, joined by criss-cross tubes. The T-loop composed springs were divided in groups of ten springs according to the caliber of the NiTi wire, handles height, horizontal activation or variations of preactivation radius or thickness of the wire rods. The springs were tested in the OFT device (Orthodontic Force Tester) for measuring orthodontic force system. Mmultivariate analysis profiles was used to compare the groups along the deactivation and possible interaction between the variables under study. It was observed that composed T-loop springs showed adequate horizontal force average for en mass retraction 0.017 x 0.025 and 0.018 x 0.025 NiTi wires. The height handles and horizontal activation variables demonstrated interaction during off to the force variable, however, have not shown this relationship to moment and M:F. It was considered that the best design of T-loop was 7mm height, 7mm horizontal activation and pre-activation radius 6mm. It was concluded that composite NiTi T-loop springs showed adequate properties for en masse retraction...(Complete abstract electronic access below)